MENTAL ACCOUNTING IN PERSONAL FINANCIAL MANAGEMENT FOR YOUTH AT BETHEL INDONESIA CHURCH (GBI) MOJOPAHIT JEMBER - Pramono, Amelia Felicia; Kusuma, Dedy Wijaya; Sari, Nurshadrina Kartika (Journal of Applied Finance and Accounting, 2024)
This research has several objectives, namely to find out the views of the young generation of GBI Mojopahit Jember regarding the mental phenomenon of accounting and how they manage their personal finances. The phenomenon in this research is that there are offerings and tithes that must be given to the Church every month. The method used in this research is a qualitative descriptive method. The samples used in this research were 7 young people at GBI Mojopahit Jember who had the criteria of being over 20 years old and having worked for at least 1 year and were used as the subjects of this research. The data sources for this research were obtained from interviews and observations. The results of this research can be concluded that most of them do not understand accounting mentality, but without realizing it they have applied accounting mentality. in their daily life. They have carried out planning, management, recording and evaluation of their personal finances. The notes taken are not very detailed, only a rough idea. For them, mental accounting is very influential in everyday life, one of which is in making decisions when buying goods. Youth at GBI Mojopahit are advised to go back to recording your finances in detail, not just lines just big and more disciplined management of their personal finances independently as well strengthen self-control to avoid waste.